Extent and consequences of tropical forest degradation: Successive policy options for Bangladesh - Kibria, M.G.; Rahman, S.A.; Imtiaj, A.; Sunderland, Terry C.H. (2011)
This paper is conceived at a time when new paradigms are sought for the development of a framework to deal with the problem of forest resources degradation. Deforestation in Bangladesh, has reached an alarming rate in recent years. The forest coverage of Bangladesh is one of the lowest and the deforestation rate is the highest of any country in the world. Coupled with the process of deforestation, flawed afforestration programmes have seriously exposed Bangladesh to environmental vulnerability. Considering this situation various strategies should be taken at different levels. The main objective of this paper is to suggest the possible steps that Bangladesh could halt and reverse the trend of deforestation. An extensive literature review and structured interviews of key informants have been used to collect relevant information to understand the reasons and consequences of forest degradation in the country. Based on the information gathered, this paper suggests some positive steps where the Government could be the main mitigating actor by implementing integrated programmes, which will also ensure mass awareness and wider impact.